Selection of A Roll Cage Assembly for The FSAE Racing Car Via Priority and Design Matrix - Muhammad Izzat Nor, Ma'arof; Nur Qistina, Jamaludin; Nurzaki, Ikhsan; Suresh, Akshith; Girma, Tadesse Chala (INTI International University, 2020)
The roll cage is an additional structural brace mounted onto the chassis of a vehicle (most prominently a car) for the purpose of protecting the driver from injuries in the event of vehicular roll-over. The structure must be able to endure all the forces from the roll-over acting upon it. Hence, the safety of the driver could be ensured via well-engineered roll-cage from the perspective of structural design, strength and stiffness. The objective of this study was, therefore, to select the optimal roll cage assembly for the INTI’s University FSAE racing car for off road usage. The selection was made with the criteria in keeping the manufacturing cost to be at minimal, yet, without compromising the safety of the driver. For this study, the priority and design matrix were used in the selection of the roll cage. It was apparent from the matrix that Design B scored the highest value, hence, chosen to be the optimal design. Major influence for the decision was due to its higher safety rating despite its lower performance when compared to Design A. Moreover, there were not much significant differences between the two designs for the cost, fabrication and ergonomics factors, which further highlights the choice for Design B. For future studies, it is recommended to perform structural analysis on the selected Design B in ensuring the overall performance given by the design.